1995
DOI: 10.1128/mcb.15.4.1999
|View full text |Cite
|
Sign up to set email alerts
|

A New Class of Histone H2A Mutations in Saccharomyces cerevisiae Causes Specific Transcriptional Defects In Vivo

Abstract: Nucleosomes have been shown to repress transcription both in vitro and in vivo. However, the mechanisms by which this repression is overcome are only beginning to be understood. Recent evidence suggests that in the yeast Saccharomyces cerevisiae, many transcriptional activators require the SNF/SWI complex to overcome chromatin-mediated repression. We have identified a new class of mutations in the histone H2A-encoding gene HTA1 that causes transcriptional defects at the SNF/SWI-dependent gene SUC2. Some of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
95
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(97 citation statements)
references
References 79 publications
2
95
0
Order By: Relevance
“…However, additional results strongly support our hypothesis of Act3p being a component of chromatin that directly interacts with core histones in vivo: complex(es) containing both Act3p and histone H2A (and probably other proteins), could be isolated from living cells (Figures 5 and 6). Furthermore, genetic data from the Winston laboratory support our biochemical results, because they have demonstrated genetic interactions between ACT3 and particular mutations in an H2A gene (Hirschhorn et al, 1995;Pinto and Winston, personal communication).…”
Section: Act3p Binds To Core Histones In Vitro and In Vivosupporting
confidence: 56%
“…However, additional results strongly support our hypothesis of Act3p being a component of chromatin that directly interacts with core histones in vivo: complex(es) containing both Act3p and histone H2A (and probably other proteins), could be isolated from living cells (Figures 5 and 6). Furthermore, genetic data from the Winston laboratory support our biochemical results, because they have demonstrated genetic interactions between ACT3 and particular mutations in an H2A gene (Hirschhorn et al, 1995;Pinto and Winston, personal communication).…”
Section: Act3p Binds To Core Histones In Vitro and In Vivosupporting
confidence: 56%
“…Namely, in both mutants several cellular proteins newly appeared or increased, and some other proteins disappeared or decreased quantitatively. These results together suggested that the H1 variants (and the core histone variants) play individual particular roles in certain biological events including gene expression, like those in yeasts (Norris & Osley 1987;Norris et al 1988;Carr et al 1994;Hirschhorn et al 1995;Megee et al 1995), Xenopus (Bouvet et al 1994), and Tetrahymena thermophila (Shen & Gorovsky 1996).…”
Section: Discussionmentioning
confidence: 91%
“…Many in vivo studies have been performed on the new nature of core histones-in addition to the vital role in chromatin organization mentioned above, especially in yeasts (Hereford et al 1982;Meeks-Wagner & Hartwell 1986;Norris & Osley 1987;Osley & Lycan 1987;Clark-Adams et al 1988;Norris et al 1988;Grunstein 1990;Carr et al 1994;Hirschhorn et al 1995)because gene replacement experiments on them can be carried out easily. Moreover, it has been reported that in Saccharomyces cerevisiae, the deletion of H4 N-terminal residues 4-23 or mutagenesis of the acetylatable lysines in this region decreases the activation of the GAL1 promoter, while the deletion of N-terminal residues 4-15 of H3 or the mutagenesis of the acetylatable lysines causes a hyperactivation of GAL1 (Fisher-Adams & Grunstein 1995).…”
Section: Introductionmentioning
confidence: 99%
“…The plasmids B155 (Libuda and Winston 2006), pSAB6 (Hirschhorn et al 1995), pDL1 (Libuda and Winston 2006), pDL2 (Libuda and Winston 2006), pMR102 (Mann and Grunstein 1992), pHB59 (Hirschhorn et al 1992), pCC64 (Clark-Adams et al 1988, and pCC65 (Clark-Adams et al 1988) have been described previously. pDM1 was constructed by amplifying the HHT2-HHF2 locus from plasmid pCC65 (Clark-Adams et al 1988) and ligating it into pRS416 (Brachmann et al 1998) after digestion with HindIII and BamHI.…”
Section: Methodsmentioning
confidence: 99%